DURABILITY OF CONCRETE WITH BINDER BASED ON SULFOCALCIC FLY ASH - Rostislav Šulc; Matouš Krása; Petr Formáček (Acta Polytechnica CTU Proceedings, 2019)
This paper deals with the durability of concrete with binder based on sulfocalcic fly ash. At the beginning, in the theoretical part, there is a research on the frost resistance of concrete, its resistance to chemical thaw substances and measures to extend the durability of the concrete. There is also a part about sulfocalcic fluid fly ash and concrete. Practical part is devoted to individual input materials and experimental procedures. There is also described the methodology of the design of the individual mixtures and the results from the tests and their comparison.